RACIAL TENSIONS IN 19TH CENTURY AMERICA AS DEPICTED IN TWAIN’S WORKS - Fakhri Ahmad Baihaqi; Leilani Azalia Putri; Resti Rosmawati; Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to provide an overview of 19th century life in the novel The Adventure of Huckleberry Finn by Mark Twain from the conflict experienced by the main character. The researcher explored the relationship between characters and how it led to the issue of racial conflict as discussed in this study. The results of this study found that life in the 19th century as depicted in the novel The Adventure Of Huckleberry Finn shows the life of the people of the United States of America which is very full of racism and slavery of white people against black people.